The Effect of Science Learning on Students' Critical Thinking Ability: A Review - Pratiwi, Rosi; Doyan, Aris (Balai Publikasi Indonesia, 2024)
Critical thinking ability is one of the high-level thinking abilities in solving problems. Several learning models can be applied to improve students' critical thinking skills. Some of these models include problem based learning, discovery learning, project based learning, and so on. This research is a literature study or literature review of 25 articles related to students' critical thinking abilities. The articles reviewed are articles published during the last 5 years, 2018 to 2022. Based on the results of a literature review that was carried out on 25 national and international articles, the highest average score for critical thinking ability was 92.56. This value was obtained by applying the discovery learning model through integrated science practicum activities. Therefore, it can be concluded that the discovery learning model is the most effective model for improving students' critical thinking abilities. The value of critical thinking ability that most often appears in the range of 71-80 in 11 articles.